(untitled) (Journal of Partial Differential Equations, 2019)
Invariant manifolds are complicate random sets useful for describing and understanding the qualitative behavior of nonlinear dynamical systems. The purpose of the present paper is try to approximate smooth stable invariant manifolds for a type of stochastic partial differential equations with multiplicative white noise near the fixed point. Two examples are given to illustrate our results.